(untitled) (Journal of the College of Basic Education, 2026)
This study was aimed to In vitro study the activity of silver nanoparticles synthesized from Capparis spinosa fruits against azole resistant Candida spp.. 120 samples were taken from 62 women with VVC and 58 samples were collected from children infected with Oral Thrush from Baghdad Hospital from February to June 2022. Microscopical examination, cultural examination to detect on Candida spp. The effect of Capparies spinosa silver nanoparticles (AgNPs) against Candida spp. viability was measured by MTT method. Synergistic effect of AgNPs with Fluconazole resistant Candida spp. was performed by MTT assay, well diffusion test .The effect of silver nanoparticles (AgNPs) synthesis from Capparis spinosa on viability of Candida spp. showed the highest inhibition percentage, the highest inhibition percentage was (88.15 and 91.42) % in C. albicans (V2) and C. lusitaniae (O38) respectively, while the lowest inhibition percentage was (77.77 and 76.31) % in C. albicans (V18) and C. lusitaniae (O36) respectively, and showed that the synergistic effect between AgNps- fruits extract with fluconazole was less than AgNps fruits extract alone and fluconazole alone. The results of statistical analysis showed significant (p≤ 0.05) between treatment and control of all isolates.